APLIKASI PENGUKURAN RISIKO DAN PENGINGAT WAKTU REPOSISI UNTUK MENURUNKAN RISIKO LUKA TEKAN - Karmandika, Ardhi Henda; Andodo, Candra (Universitas Sam Ratulangi, 2023)
Background: Pressure ulcers are localized injuries to the skin and/or tissue overlying bone prominences, resulting from pressure or a combination of pressure and friction. Pressure ulcers constitute a serious issue that afflicts patients with mobility impairments. Various technologies have been developed to facilitate healthcare convenience. Android applications in the healthcare category provide users with health-related information without temporal or spatial constraints, assisting them in achieving health-related goals, including the prevention of health disorders. Objective: This study has developed an application capable of generating pressure ulcer risk scores and recommending repositioning reminders based on user-input data, utilizing the forward chaining method. This application aids users in assessing the degree of pressure ulcer risk they face and in performing repositioning at recommended intervals accurately, thereby reducing pressure ulcer risk scores. Methods: This research is an experimental study employing a one-group pre-test-post-test design with a sample size of 30 respondents. Result: Data obtained from user histories indicate that respondents under surveillance using the repositioning reminder application experienced a decrease in pressure ulcer risk scores on the second day following the application's use, with a mean of .267 and a standard deviation of 3.741, exhibiting a significance value of .699 >α (0.05). Conclusion: This repositioning time and reminder application can serve as a new solution in pressure ulcer prevention. Keywords: application; Android; pressure ulcers